Good or bad? : students’ perspectives on software quality - Hrefna Namfa Finnsdóttir 1996- (2024)
People interact with various software daily. This includes software that they choose to use and software that they must use because of their work or other circumstances. Companies often require their customers to use their software for their services, such as online banking and public transportation apps. This underscores the importance of developing high-quality software, which is not a simple task. To achieve this, it is crucial to understand which quality attributes to focus on in development. User involvement has been shown to contribute to high-quality software. Thus, gathering user perspectives on important quality attributes is valuable. Given the limited research on software quality attributes from users' perspectives, this study provides new insights into what quality attributes users consider important for well- and badly-designed software. Data was collected from an assignment in the Software Requirements and Design course at Reykjavik University. In the assignment, students named three well-designed and three badly designed software systems, websites, and apps, along with reasons for their opinions. These submissions were organized, categorized, and analyzed. The findings revealed Spotify, Discord, and YouTube as top choices for well-designed software, while Piazza, Klappið (an app for public buses in Reykjavík), and Facebook were most frequently cited as badly designed. The study identified that to create high-quality software, developers should prioritize usability, functionality, and user interface design. This is done by selecting relevant features that are efficient and reliable while ensuring an organized, simple, and easy-to-use interface. Fólk er í samskiptum við allskonar hugbúnað daglega. Þar á meðal hugbúnað sem þau velja sjálf að nota og hugbúnað sem þau þurfa að nota vegna vinnu sinna eða annarra aðstæðna. Fyrirtæki krefjast oft þess að viðskiptavinir þeirra noti hugbúnað fyrir þjónustu sína, til dæmis í bankaviðskiptum og samgöngum. Þetta undirstrikar mikilvægi þess að þróa hágæða ...